1990
DOI: 10.1063/1.345337
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence studies of free-standing quantum boxes

Abstract: We report photoluminescence measurements made on free-standing, lattice-matched GaAs/AlGaAs and pseudomorphic InGaAs/GaAs quantum boxes fabricated by laterally patterning quantum wells using electron-beam lithography and either reactive ion etching or ion beam milling. At temperatures below 10–20 K the luminescence efficiency of most of the GaAs quantum-box arrays tends to scale with the volume of quantum-well material remaining after processing even for the smallest boxes which have lateral dimensions of only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…RIE processing does not always lead to a change of PL behaviour from linear to super-linear. For example, according to [13], RIE-etched GaAs/AlGaAs QDs showed a linear dependence of PL at low temperatures on the excitation intensity (the excitation energy was below the bandgap of AlGaAs) even for less efficiently emitting arrays, but the authors reported a strong quenching of the PL in similar InGaAs/GaAs etched dots, to be in contrast with our findings. Indeed, the PL of InGaAsN : Sb/GaAs dots is rather strong even at room temperatures but exhibits moderate superlinear behaviour, characteristic of nonradiative recombination.…”
Section: Photoluminescence Measurementscontrasting
confidence: 99%
See 1 more Smart Citation
“…RIE processing does not always lead to a change of PL behaviour from linear to super-linear. For example, according to [13], RIE-etched GaAs/AlGaAs QDs showed a linear dependence of PL at low temperatures on the excitation intensity (the excitation energy was below the bandgap of AlGaAs) even for less efficiently emitting arrays, but the authors reported a strong quenching of the PL in similar InGaAs/GaAs etched dots, to be in contrast with our findings. Indeed, the PL of InGaAsN : Sb/GaAs dots is rather strong even at room temperatures but exhibits moderate superlinear behaviour, characteristic of nonradiative recombination.…”
Section: Photoluminescence Measurementscontrasting
confidence: 99%
“…The spectra obtained with the InGaAsN : Sb/GaAs dots (solid lines in figure 4) and wells (dotted line in figure 4) show emission peaks centred at 0.96 eV and 1.01 eV, respectively. Note that the room temperature PL can be readily obtained in the etched QDs, whereas the PL from similarly processed InGaAs/GaAs quantum boxes, for example, was previously reported to be nearly absent [13]. Also, the minimum PL peak broadening demonstrates the high size uniformity of the dots.…”
Section: Photoluminescence Measurementsmentioning
confidence: 92%
“…There was a decrease by a factor of 0.5 for the 50 Â wells and of 0.2 for the 100 À wells in comparison with the luminescence efficiency of the unetched structures. This degradation may be due to a high non-radiative recombination velocity at the sidewalls surface, but comparison with other research work [8], in which quantum-dots were fabricated from the same material as this work, the higher temperature applied in our experiment may also be responsible since temperature-enhanced diffusion enables more excitons to reach surface states. The difference between the degradation factors for the 50 À and 100 Â wells may be explained by the lower carrier diffusion coefficient for the narrower quantum-wells which results from the carrier localisation effect [13].…”
mentioning
confidence: 77%
“…We cite here only some representative manuscripts on this topic for the interested reader, and underline that the community seeking optical effects quickly realized, during the eighties, that top-down approaches (including implantation) could bring with them difficult to eliminate distributed defects affecting widespread good optical features, uniformity and control. 31,32,33,34,35,36,37,38,39 This has been one of the main drive ("There is growing, universal evidence that one-dimensional (1D) and OD nanostructures lead to diminished luminescence quality when compared to 2D or 3D heterostructures") 40 to search for bottom up self-assembled structures, which showed stronger promises once tested, and, had also effectively begun in the early eighties, sometimes through chance findings as we will discuss.…”
Section: Top-down Vs Bottom-upmentioning
confidence: 99%